2011
DOI: 10.1136/thx.2010.145490
|View full text |Cite
|
Sign up to set email alerts
|

Virtual bronchoscopic navigation combined with endobronchial ultrasound to diagnose small peripheral pulmonary lesions: a randomised trial

Abstract: BackgroundBronchoscopy using endobronchial ultrasound (EBUS) can help to diagnose small peripheral pulmonary lesions. However, although biopsy sites can be confirmed, a bronchoscope cannot be guided in EBUS. Virtual bronchoscopic navigation (VBN) can guide a bronchoscope with virtual images, but its value has not been confirmed.MethodsThis prospective multicentre study examines the value of VBN-assisted EBUS for diagnosing small peripheral pulmonary lesions. 199 patients with small peripheral pulmonary lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
219
4
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(242 citation statements)
references
References 36 publications
14
219
4
5
Order By: Relevance
“…Furthermore, multiple studies have demonstrated that VB may improve diagnostic performance of radial EBUS [10,30,31]. In centres where these adjunct tools are not utilised, the incremental gain in diagnostic performance with addition of EMN may be greater than observed in our current study.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, multiple studies have demonstrated that VB may improve diagnostic performance of radial EBUS [10,30,31]. In centres where these adjunct tools are not utilised, the incremental gain in diagnostic performance with addition of EMN may be greater than observed in our current study.…”
Section: Discussioncontrasting
confidence: 55%
“…Several studies have reported that EBUS-GS with VBN was safe and effective for diagnosing small peripheral lung lesions [22,23]. Furthermore, another study reported that diagnostic yield for small peripheral lung lesions is significantly increased when VBN is added to EBUS-GS [24].…”
Section: Introductionmentioning
confidence: 99%
“…107 In this trial, diagnostic yield was higher for the VBN-assisted procedure (80%) than for the unassisted procedure (67%).…”
Section: In the Individual With A Solid Indeterminate Nodule That Shmentioning
confidence: 90%